2018
DOI: 10.1101/427294
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Infection-generated electric field in gut epithelium drives bidirectional migration of macrophages

Abstract: Many bacterial pathogens hijack macrophages to egress from the port of entry to the lymphatic/blood-stream, causing dissemination of life-threatening infections. However, the underlying mechanisms are not well understood. Here, we report that Salmonella infection generates directional electric fields (EF) in the follicle-associated epithelium of mouse cecum. In vitro application of an EF, mimicking the infection-generated electric field (IGEF), induces directional migration of primary mouse macrophages to the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 96 publications
(97 reference statements)
0
9
0
Order By: Relevance
“…In the field of macrophages, human monocyte-derived macrophages (dcEF: 5–300 mV/mm, 2 h) [ 9 ], mouse bone marrow-derived macrophages (dcEF: 300 mV/mm, 4 h) [ 11 ], mouse peritoneal macrophages (PMs) and bone marrow-derived macrophages (BMDMs) (dcEF: 400 mV/mm, 3 h) [ 12 ] have been used to study various biological effects of electric fields on macrophages. The interpretation of the above results suggests that the proper stimulation condition of an electric field on cells is in the range of 100–400 mV/mm (0.5–8 h).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the field of macrophages, human monocyte-derived macrophages (dcEF: 5–300 mV/mm, 2 h) [ 9 ], mouse bone marrow-derived macrophages (dcEF: 300 mV/mm, 4 h) [ 11 ], mouse peritoneal macrophages (PMs) and bone marrow-derived macrophages (BMDMs) (dcEF: 400 mV/mm, 3 h) [ 12 ] have been used to study various biological effects of electric fields on macrophages. The interpretation of the above results suggests that the proper stimulation condition of an electric field on cells is in the range of 100–400 mV/mm (0.5–8 h).…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Yaohui Sun et al showed that a Salmonella infection generates an electric field in the gut epithelium of the mouse cecum, which drives the bidirectional migration of macrophages. By using primary mouse peritoneal macrophages (PMs) and bone marrow-derived macrophages (BMDMs), they mimic the infection-generated electric field by exposing macrophages with electric field (dcEF: 400 mV/mm, 3 h), and they also found that Salmonella infection switches macrophage galvanotaxis from the anode to the cathode [ 12 ]. Taken together, the above studies suggest that the electric field is a new regulatory element that determines the function of macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…To explore this possibility and to gain insights into the mechanism of electrotaxis in vivo, we investigated how neural crest cells sense and transduce endogenous electric fields into a directional cue. Most of the proteins reported to mediate electrotaxis are part of the cell selfpolarity 20,21 or cell-substrate adhesion 22,23 machineries and few molecules have been shown to specifically mediate electrotaxis in vitro [24][25][26][27] . Hence, the precise mechanism used by cells to transduce electric fields into a directional response in vivo remains unclear.…”
Section: Mainmentioning
confidence: 99%
“…Salmonella initially colonizes the small intestine and invades IECs, overcoming the mucosal barrier and manipulating the immune response through translocation of various effector molecules [28][29][30] . It can bypass humoral immunity by hijacking phagocytes to egress from the gut into the lymphatic system or bloodstream, potentially causing life-threatening systemic infections 31 . The above-described influence of HIF-1 on cellular immune functions as well as tight sealing of the intestinal wall therefore led us to investigate its role during gastrointestinal infections, using Salmonella enterica subsp.…”
Section: Introductionmentioning
confidence: 99%